(untitled) (Architecture Image Studies, 2025)
This research article presents broad-based review on e-waste management at the Sultanate of Oman. It describes the types and practices of handling e-waste. The article also explores the collection and transportation of e-waste from various companies to the recycling hub. In addition, this article focuses on the opportunities for sustainable e-waste management including environmental challenges and studies relevant literature on handling logistics routing and fixing up warehouses in a particular city.